Aplicación de estrategias de mediación para mejorar la comprensión de textos escritos en estudiantes de 3° grado de Educación Primaria - Huatangare Alarcón, Dayne Mileni (2022)
The present work of professional competence aims to demonstrate that the application of _x000D_ mediation strategies improves reading comprehension in elementary school children and based _x000D_ on my experience I can affirm that mediating the learning of our students and providing them _x000D_ with all the resources and tools will facilitate the construction of their reading skills, so that they _x000D_ can make use of them and at the same time develop their own strategies and apply them in any _x000D_ school or social context. That is why we have taken into account the theories of Vygotsky and _x000D_ Feuerstein, who point out the importance of the mediation process in learning; although we _x000D_ know that the student himself already has a set of previous knowledge, it is necessary that there _x000D_ is an adult who assumes the role of mediator to facilitate that the student can achieve the highest _x000D_ levels of cognitive development. Therefore, the mediation strategies were applied in the _x000D_ development of the learning session in each of the didactic processes of the area, helping _x000D_ considerably the group of third grade students, who can understand much better any text they _x000D_ read without the need to be only from the area of communication.